Renshen Baidu powder protects ulcerative colitis via inhibiting the PI3K/Akt/NF-κB signaling pathway - Ye, Zhen; Li, Yuzheng; She, Yingqi; Wu, Mingquan; Hu, Yu; Qin, Kaihua; Li, Linzhen; Yu, Han; Zhao, Qian; Jin, Zhao; Lu, Fating; Ye, Qiaobo (Frontiers in Pharmacology, 2022)
Ulcerative colitis is a chronic and relapsing inflammatory bowel disease without satisfactory therapy recently. Renshen Baidu Powder (RSBDP) is a classical Chinese medicinal formula since Chinese Song dynasty and has been proven as an effective treatment on ulcerative colitis in clinic. However, the active ingredients and the molecular mechanism have not been fully disclosed. It is imperative to explore the active ingredients and the mechanism of RSBDP. In this study, the potential active components for ulcerative colitis in RSBDP were determined and predicted in silicon and its molecular mechanisms was also presented, in which the PI3K/Akt/NF-κB signaling pathway was recognized to be vital. Based on the prompt evidence, the pharmacodynamic and mechanistic studies of RSBDP for ulcerative colitis were implemented on TNBS-induced experimental rats. The results showed that RSBDP could ameliorate disease ac-tivity index and colon weight, improve colonic shortening and colon histology. In addition, the tumor necrosis factor-α (TNF-α), Diamine oxidase, intercellular adhesion molecule-1 and endotoxin in serum were also reduced. It is worth mentioning that the PI3K/Akt/NF-κB signaling pathway was inhibited after given RSBDP via inhibiting the phosphorylation of proteins. In conclusion, RSBDP effectively ameliorates TNBS-induced colitis rats through inhibiting the PI3K/Akt/NF-κB signaling pathway.